Mispositioned Hydrus Microstents: A Case Series Imaged with NIDEK GS-1 Gonioscope - Daniel Laroche; Alexander Martin; Aaron Brown; Sohail Sakkari; Chester Ng (Journal of Ophthalmology)
Introduction. The Hydrus microstent has become a common procedure in glaucoma surgery intended to improve outcomes of cataract surgery to lower intraocular pressure. Despite proper placement, this device can subsequently be noted to not be in the proper position. In this case series, we report mispositioned Hydrus microstents in five different patients and use NIDEK GS-1 gonioscopy. Case Report. We report five different patients who had cataract surgery and who were subsequently noted to have mispositioned Hydrus stents. No stents needed to be removed. All patients had improved vision and stable visual fields, and none required secondary surgery. Management and Outcome. In each case of mispositioned stents, vision was significantly improved and there was no inflammation or other complications noted. Discussion. Hydrus stents can be noted to be mispositioned during the post-operative period after successful insertion. This can often be well tolerated requiring no further intervention.